2011
DOI: 10.1121/1.3588779
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the number of fin whale calls recorded at different locations in the Northeast Pacific Ocean.

Abstract: A large number of fin whale calls have been observed in a 3-year ocean bottom seismometer dataset (2003–2006) over the Endeavor Ridge (48°N/129°W), a hydrothermally active area in the Northeast Pacific Ocean. Most of the vocalizations were detected during the winter months. Because zooplankton constitute an important part of fin whales’ diets, and enhanced populations of zooplankton have been observed at all depths above the Endeavor hydrothermal vents, it has been hypothesized that the fin whales could be nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The hypothesis that baleen-whales feeding in the upper ocean may be concentrated in regions of hydrothermal venting (see Weirathmueller et al, 2011) is extremely difficult to prove because of the wide ranging territories of these animals and the limitation of their diving to the upper part of the ocean. It appears that secondary production is higher in summer near the vents than offaxis, and this may be attracting larger consumers, even possibly whales.…”
Section: Implications For Higher Trophic Level Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that baleen-whales feeding in the upper ocean may be concentrated in regions of hydrothermal venting (see Weirathmueller et al, 2011) is extremely difficult to prove because of the wide ranging territories of these animals and the limitation of their diving to the upper part of the ocean. It appears that secondary production is higher in summer near the vents than offaxis, and this may be attracting larger consumers, even possibly whales.…”
Section: Implications For Higher Trophic Level Productionmentioning
confidence: 99%
“…Based on moored seismic array data, Soule and Wilcock (2013) have suggested that some of the fin whales found near Endeavour Ridge do not migrate south in the fall. In addition, the highest concentration of fin whale vocalizations near the ridge is observed in the winter months (Wilcock et al, 2009;Weirathmueller et al, 2011). Acoustic tracking of whale calls through the Endeavour Ridge seismic network (Wilcock et al, 2009;Wilcock, 2012) indicates that observed data gaps of tens of minutes when the whales stop vocalizing occur preferentially above the ridge.…”
Section: Implications For Higher Trophic Level Productionmentioning
confidence: 99%
“…In previous reporting periods, we evaluated two automated methods to detect fin calls using matched filters and spectral cross-correlation (Weirathmueller et al, 2011) and obtained call counts normalized to a uniform background noise level for sites on the Endeavour ridge, Nootka fault and middle of the Explorer and Juan de Fuca plates ( Fig. 1).…”
Section: Whale Call Densitiesmentioning
confidence: 99%
“…Whale Call Densities. In previous reporting periods, we evaluated two automated methods to detect fin calls using matched filters and spectral cross-correlation (Weirathmueller et al, 2011) and obtained call counts normalized to a uniform background noise level for sites on the Endeavour ridge, Nootka fault and middle of the Explorer and Juan de Fuca plates (Fig. 1).…”
Section: Work Completedmentioning
confidence: 99%